Outcome of single level intervertebral disc prolapse treated with interlaminar lumbar discectomy by fenestration - Ramanagouda Biradar; V.V. Mundewadi; Arravind Pillai (Al Ameen Medical College, 2016)
Background: Low back pain due to lumbar disc prolapse is the major cause of morbidity throughout the world affecting mainly young adults. Different surgical techniques for lumbar discectomy are in vogue with the aim of least possible damage to other structures while dealing with the prolapsed disc. This short term prospective study was done to assess the functional outcome interlaminar fenestration discectomy. Materials and Methods: Thirty six patients with clinical symptoms and signs of single level prolapsed lumbar intervertebral disc having radiological correlation by MRI study were subjected to disc excision by interlaminar fenestration. Outcomes were measured using the visual analogue scale (VAS) for back and leg pain, Roland-Morris score (RM) improvement and modified Macnab criteria at 3 months, 6 months and 2 years. All quantitative data were summarised using mean and standard deviation, and qualitative data using proportions. Results: Mean (SD) VAS for lower back ache and leg pain at 3 months, 6 months, and 2 years shows improvement in the overall low back pain and leg pain in patients studied. The maximum improvement in radicular pain is seen within six months after surgery and from then on not much improvement were noted. According to modified Macnab criteria outcome was good in 69.4%, fair in 22.2%, and poor in 8.3% of patients treated by fenestration surgery. Conclusion: Interlaminar lumbar discectomy by fenestration method without extensive laminectomy is effective and reliable surgical technique for treating properly selected patients with herniated lumbar disc at L4-L5 and L5-S1 levels. The results are comparable to microdiscectomy, and this may be due to the close similarity of the two procedures.